Influences of isolated gut probiotic bacteria Bacillus Licheniformis on haematological parameters of the fresh water fish cyprinus carpio (L). - C. KALAIMANI1,; K.PARVATHI,; P.SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2019)
Aquaculture is probably the quickest developing food producing division and about 50% of the world's fish is utilized for food. Probiotic microbes are really necessary for a useful impact on the specific well- being of the species and in the nutrition of the host for a healthy intestinal function.The present study aims to find out the influences of isolated gut probiotics bacteria Bacillus licheniformis on haematological parameters of the freshwater fish C.carpio.The gut probiotic bacteria Bacillus licheniformis was isolated from Labeo rohita and identified based on its biochemical test and 16s rRNA profile (GATTGGGGTGAAGTCGTAACAAGGTAGCCGTATCGGAAGGTGCG)(Seq.id.NR.118996.1). The fish in the control tank were fed only with supplementary fish feed without probiotics bacteria B.licheniformis and the fish in the experimental tank were fed with supplementary fish feed mixed with the isolated gut probiotic bacteria Bacillus licheniformis. Fishin the both tanks were fed (3% body wt of fish) twice a day that is early morning (5.30 am-6 am) and evening (5.30 pm-6 pm) regularly and the experiment was carried out for 75 days and the sample was taken from control and experimental fish on 15th, 30th, 45th,60th and 75th day of the experimental period. Significantly increased total erythrocyte count,haemoglobin level, total leukocyte count, PCV and MCV were recorded at the end of 75th day of the experimental period in the probiotic fed fish reflects the good health condition of the experimental fish.